Pengaruh Kemudahan dan Manfaat Penggunaan Shopee Paylater Terhadap Perilaku Impulse Buying - Alfinatu Nikmah; Sri Setyo Iriani (Jurnal Ilmiah Wahana Pendidikan, 2023)
This paper analyses the influence of the ease of us and usefulness of using shopee paylater on impulse buying behavior. This research uses quantitative data. The sampling technique used was non-probability sampling with the type of purposive sampling. The sample used in the study is 220 respondents. The research method used multiple linear regression analysis and data collection through questionnaires. The results showed that ease of use and usefullnes positively and significantly affected impulse buying behavior. Hypothesis testing using the t test shows that the two independent variables studied significantly influence the dependent variable behavior Impulse Buying. The Adjusted R Square figure of 0.613 indicates that 61.3% of the Impulse Buying variable can be explained by the two independent variables in the regression equation. While the remaining 38.7% is explained by other variables outside the two variables used in this study.